5-Aza-2′-Deoxycytidine Improves the Sensitivity of Endometrial Cancer Cells to Progesterone Therapy. Issue 6 (1st July 2012) - Hu, Qian; Yu, Li; Chen, Rui; Wang, Yan-ling; Ji, Lei; Zhang, Yan; Xie, Ya; Liao, Qin-ping
Abstract : Objective: Progesterone has been proven to have limited effects on endometrial cancers (ECs), mainly owing to the down-regulation of progesterone receptor (PR). Here, we explored whether 5-aza-2′-deoxycytidine (5-aza-CdR), a demethylating agent, could enhance the susceptibility of EC cells to medroxyprogesterone acetate (MPA). Methods: Ishikawa and KLE cell lines were treated with 5-aza-CdR and/or MPA. The expression of PR, PR target genes, and matrix metalloproteinase (MMP) was investigated by real-time polymerase chain reaction and Western blot. Promoter methylation was detected by methylation-specific polymerase chain reaction. The effects of 5-aza-CdR and/or MPA on cell proliferation, apoptosis, and invasion of EC cells were evaluated by 2-(4-Iodophenyl)-3-(4-nitrophenyl)-5-(2, 4-disulfophenyl)-2H-tetrazolium assay, flow cytometry, invasion assay, and gelatin zymography, respectively. Results: 5-Aza-2′-deoxycytidine significantly increased the expression of PR and its downstream targets by demethylating PR promoter in both Ishikawa and KLE cells. 5-Aza-2′-deoxycytidine combined with MPA synergistically suppressed the EC cell growth by inducing cell cycle arrest at G2/M phase and apoptosis. Furthermore, 5-aza-CdR synergized with MPA to inhibit the invasion of EC cells, perhaps owing to the down-regulation of MMP-2 and MMP-9 expression and activity. Conclusions: 5-Aza-2′-deoxycytidine and MPA synergistically inhibit EC cell growth and invasion. Their combined use may provide a new effective therapeutic opportunity for endometrial carcinoma.